2017
DOI: 10.1016/j.vascn.2017.02.021
|View full text |Cite
|
Sign up to set email alerts
|

Proarrhythmia liability assessment and the comprehensive in vitro Proarrhythmia Assay (CiPA): An industry survey on current practice

Abstract: Proarrhythmia liability assessment in drug development presently includes study types consistent with CiPA. It is anticipated that CiPA will develop into a workable solution to the concern that proarrhythmia liability testing remains suboptimal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 57 publications
1
17
0
Order By: Relevance
“…Our experiences with hSC-CM indicate that pro-arrhythmia risk assessment in hSC-CM is not ready for primetime. Our findings are consistent with the outcome of a recent industry survey conducted by the Safety Pharmacology Society (Authier et al, 2017 ), which reported that only 21% of responders considered hSC-CM representative of adult cardiomyocytes and provide reliable data as a nonclinical safety assay.…”
Section: Introductionsupporting
confidence: 92%
“…Our experiences with hSC-CM indicate that pro-arrhythmia risk assessment in hSC-CM is not ready for primetime. Our findings are consistent with the outcome of a recent industry survey conducted by the Safety Pharmacology Society (Authier et al, 2017 ), which reported that only 21% of responders considered hSC-CM representative of adult cardiomyocytes and provide reliable data as a nonclinical safety assay.…”
Section: Introductionsupporting
confidence: 92%
“…Consistent with the SPS tradition of publishing industry surveys on SP-related topics to inform on trends and practices in the field, [13][14][15][16][17] this survey explored important additional facets of CV SP. The present survey aimed to further examine current practices and strategies that are used principally by those drug safety scientists working in the pharmaceutical industry relative to CV SP model selection, study design, and data interpretation.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, in a previous SPS survey, 17 the potential limitations to the use of hiPSC-CM in drug safety evaluations appeared numerous and included aspects such as reliability of the cells to represent adult cardiomyocyte phenotypes, stability of cardiac ion channel expression, and the financial impact to establish the assay. [17][18][19][20] However, responses in the current survey suggest that the implementation and use of hiPSC-CM has become less formidable, with 23% of responders now reporting frequent use of this in vitro assay. While this is likely attributed to both technological advances achieved with advanced engineering of hiPSC-CM as well as a plethora of published data using a multitude of drugs in recent years, there remains some concerns relative to the adult phenotype of the cells used in these emerging in vitro models.…”
Section: Discussionmentioning
confidence: 99%
“…Additional references are provided. [64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81][82]…”
Section: The Comprehensive In Vitro Proarrhythmia Assaymentioning
confidence: 99%